Novel use of communication technology to improve nurse-physician communication, teamwork, and care coordination during bedside rounds*. (2nd January 2018) - Wickersham, Alexis; Johnson, Krista; Kamath, Aparna; Kaboli, Peter J.
ABSTRACT: Background: Inter-professional bedside rounding has been used to reduce communication deficits and improve patient outcomes. Our objective was to evaluate nurse and physician participation in inter-professional bedside rounds and perceptions of communication, teamwork, and care coordination, through a quality improvement (QI) intervention. Method: A web-based survey was completed by attending and resident physicians and nurses working on the general medical wards of an academic-affiliated Veteran's Health Administration Hospital (VHA). Responses were assessed using the chi-square statistic. Qualitative responses were grouped into themes for analysis to guide the intervention. A pre-existing electronic communication device was utilized in a novel way by resident physicians to facilitate nursing participation in bedside rounds. Perceptions of communication, teamwork, and care coordination between nurses and physicians prior to and after introduction of the electronic communication device were assessed. Direct observation was used to assess nursing presence during physician team rounds. Results: Following the intervention, both nurses and physicians agreed more nurses were alerted by physicians when rounds began and better communication between nurses and physicians occurred. However, technological barriers limited sustainability. Nursing presence on rounds increased from a baseline of 16.5% to 36% post-intervention. Conclusions: Implementation of a voice-activated, communication device on rounds facilitated improvement in perceptions of communication, teamwork, and care coordination, which may ultimately impact cultural change and patient outcomes.